2010
DOI: 10.3109/08923973.2010.518618
|View full text |Cite
|
Sign up to set email alerts
|

Pentapeptide sharing betweenCorynebacterium diphtheriatoxin and the human neural protein network

Abstract: We describe the pentapeptides shared between the Corynebacterium diphtheria toxin and the human proteins associated with fundamental neural functions. We report that diphtheria toxin pentapeptides are spread among human antigens such as tuberous sclerosis proteins 1 and 2, reelin, contactin-4, neuroligins, semaphorin-5A, sodium channel protein type 1 subunit α, Williams-Beuren syndrome chromosomal region 1 protein, Williams-Beuren syndrome chromosomal region 20A protein. Williams-Beuren syndrome chromosomal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 129 publications
0
14
0
Order By: Relevance
“…For diverse pathogens, these human homologues appear to be concentrated within networks that are relevant to diseases in which the pathogen is implicated [35, 37, 38, 179, 180]. This problem is extensive and concerns all human proteins, along their entire length.…”
Section: Discussionmentioning
confidence: 99%
“…For diverse pathogens, these human homologues appear to be concentrated within networks that are relevant to diseases in which the pathogen is implicated [35, 37, 38, 179, 180]. This problem is extensive and concerns all human proteins, along their entire length.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the human proteome contains multiple sequences (pentapeptides or longer contiguous or gapped consensus) identical to those within numerous viral and microbial proteins, with the human matches concentrated within networks relevant to diseases in which the pathogen is implicated (Kanduc et al, 2008;Bavaro et al, 2011;Trost et al, 2011). This phenomenon concerns all human proteins.…”
Section: Pathogen-derived Autoimmunitymentioning
confidence: 99%
“…Microbial proteomes massively overlap human proteins [34][35][36][68][69][70] in a tight network of metabolic interactions that may carry pathologic sequelae in the host. Indeed, bacterial organisms may interfere with the apoptotic apparatus [71], manipulate and subvert host-cell pathways [72], and interfere with the host immune system and mechanisms [73].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…In general, microbial-versushuman cross-reactions are expected phenomena in infections. Indeed, numerous reports highlight a high level of microbial-versus-human peptide overlap [34][35][36], and B. pertussis is no exception. In fact, it was found that the number of B. pertussis pentapeptide occurrences in the human proteome (including multiple occurrences) is 6,271,766, with 35,998 human proteins involved in the pentapeptide overlap [35].…”
mentioning
confidence: 97%